Protective cover and battery module
By using an adhesive layer with an island-shaped part and a mesh structure in the battery module to connect the heat insulation part and the protective cover of the inorganic fiber sheet, the problem of insufficient thermal insulation performance in the prior art is solved, and effective heat insulation and fire protection of the battery module are achieved.
Patent Information
- Application Number
- CN202420606851.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Priority Date
- 2024-02-09
- Filing Date
- 2024-03-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2034-03-27
AI Technical Summary
In the prior art, the multilayer materials used in lithium-ion secondary batteries cannot obtain sufficient thermal insulation performance and cannot effectively prevent flame diffusion when thermal runaway is not controlled.
A protective cover is used, which consists of a heat insulating member, an inorganic fiber sheet and an adhesive layer. The adhesive layer bonds the heat insulation member to the inorganic fiber sheet and has a plurality of island-shaped portions and mesh structures to improve thermal insulation performance.
It realizes effective heat insulation and fire protection for the battery module, can suppress flame diffusion when thermal runaway, and maintain excellent thermal insulation effect.
Smart Images

Figure CN222601251U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to a protective cover and a battery module provided with the protective cover. Background Art
[0002] In recent years, lithium ion secondary batteries have been used in electric vehicles, etc., for environmental protection. However, lithium ion secondary batteries use organic electrolytes, so if they catch fire during thermal runaway, there is a possibility that flames will be generated and the battery pack will be damaged.
[0003] As a countermeasure thereto, a multilayer material for use as a heat insulating barrier in an electric energy storage system is proposed, for example, in Patent Document 1. The multilayer material includes at least one inorganic fabric layer bonded to a nonwoven fabric layer containing inorganic particles and inorganic fibers by an inorganic adhesive containing at least 99% by weight of an inorganic component and 0.01% by weight or more and less than 1% by weight of an organic additive.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2021 / 022130 Utility Model Content
[0007] Technical problems to be solved by the utility model
[0008] However, as the capacity of recent batteries increases, the number of stacks also increases, and the amount of organic electrolyte also increases, and therefore safety measures are strongly required when thermal runaway occurs in batteries. However, the multilayer material described in Patent Document 1 cannot achieve sufficient thermal insulation performance.
[0009] The utility model is completed in view of the above-mentioned technical problems, and its purpose is to provide a protective cover and a manufacturing method thereof, as well as a battery module that can protect the heat insulating member from the impact of splashes and can further improve the heat insulation performance.
[0010] Means for solving technical problems
[0011] The above-mentioned object of the present invention is achieved by the following structure involving the protective cover.
[0012] A protective cover is provided.
[0013] The protective cover has:
[0014] Thermal insulation;
[0015] Inorganic fiber sheets; and
[0016] an adhesive layer that joins the thermal insulation member to the inorganic fiber sheet,
[0017] When viewed in a lamination direction of the heat insulating material and the inorganic fiber sheet, the adhesive layer includes a plurality of island-shaped portions and a mesh-shaped portion connecting the plurality of island-shaped portions to each other.
[0018] Moreover, the preferred embodiment of the present invention regarding the protection cover relates to the following structure.
[0019] Furthermore, a gap is provided between the inorganic fiber sheet and the thermal insulation member.
[0020] Furthermore, in the inorganic fiber sheet, the organic material constituting the adhesive layer intrudes into a region from a surface in contact with the adhesive layer to an inner region.
[0021] Furthermore, a portion of the inorganic particles contained in the thermal insulation member is immersed in the adhesive layer.
[0022] In addition, the above-mentioned object of the present invention is achieved by the following structure related to the battery module.
[0023] A battery module is provided, the battery module comprising:
[0024] The aforementioned protective cover;
[0025] Batteries; and
[0026] A battery case houses the protective cover and the storage battery.
[0027] In addition, a preferred embodiment of the present invention regarding a battery module relates to the following structure.
[0028] Furthermore, the battery housing has a top surface, a side wall surface and a bottom wall surface inside thereof.
[0029] The protective cover is installed in the battery case and is arranged so that the heat insulating member faces at least one selected from the top surface, the side wall surface, and the bottom wall surface.
[0030] Utility Model Effect
[0031] The protective cover of the utility model is obtained by bonding an inorganic fiber sheet and a heat insulating member through an adhesive layer. The heat insulating member contains at least one of inorganic fiber and infusible fiber, so it has excellent heat insulation performance and fireproof performance. In addition, since it has an inorganic fiber sheet, it is possible to prevent splashing objects from directly colliding with the heat insulating member. Furthermore, since the adhesive layer has a unique structure, it is possible to improve the heat insulation performance while maintaining the bonding performance.
[0032] Furthermore, the battery module of the present invention has the protective cover of the present invention provided in the battery case accommodating the battery, so that damage caused by splashing during thermal runaway can be suppressed, and even if a flame is generated, it can be more reliably prevented from spreading to the outside. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 1 is a schematic cross-sectional view showing the protective cover according to the present embodiment.
[0034] Figure 2 It is observed along the stacking direction. Figure 1 Schematic diagram of the adhesive layer in the protective cover shown.
[0035] Figure 3 Yes means Figure 1 A schematic diagram of a cross section of a portion of a protective cover is shown.
[0036] Figure 4 This is a schematic diagram showing an example of a method for manufacturing a protective cover according to an embodiment of the present invention.
[0037] Figure 5 It is a schematic cross-sectional view showing a battery module according to an embodiment of the present invention.
[0038] Description of symbols
[0039] 1: Protective cover;
[0040] 2: Thermal insulation;
[0041] 3: Inorganic fiber sheet;
[0042] 4: Adhesive layer;
[0043] 5: insular part;
[0044] 6: reticular part;
[0045] 7: gap;
[0046] 8: Inorganic particles;
[0047] 14: Adhesive material;
[0048] 100: battery module;
[0049] 110: Battery;
[0050] 120: Battery casing. DETAILED DESCRIPTION
[0051] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. In addition, the present invention is not limited to the embodiments described below, and can be implemented with arbitrary changes within the scope not departing from the gist of the present invention.
[0052] [Protective cover]
[0053] Figure 1 : is a schematic cross-sectional view showing the protective cover of this embodiment. Figure 2 It is expressed by observing along the stacking direction. Figure 1 A schematic diagram of the adhesive layer of the protective cover is shown, Figure 3 Yes means Figure 1 A schematic diagram of a cross section of a portion of the protective cover shown. Figure 1 As shown, the protective cover 1 includes a heat insulating material 2 containing inorganic particles, an inorganic fiber sheet 3, and an adhesive layer 4 for bonding the heat insulating material 2 and the inorganic fiber sheet 3. The adhesive layer 4 contains an organic material.
[0054] like Figure 2 As shown, when viewed in the stacking direction parallel to the stacking direction of the heat insulating material 2 and the inorganic fiber sheet 3, the adhesive layer 4 has a plurality of island portions 5 and a mesh portion 6 that interconnects the plurality of island portions 5. More specifically, the mesh portion 6 has a plurality of linear bodies that partially cross and extend in a plurality of various directions, thereby constituting the mesh portion 6. Furthermore, the mesh portion 6 interconnects the plurality of island portions 5.
[0055] The linear bodies constituting the mesh portion 6 are not limited to linear bodies, but may be curved linear bodies. In addition, the linear bodies extend in multiple directions from the intersections where the linear bodies intersect each other, but the directions are not limited to four directions, and may be three directions or five or more directions. The width of the linear bodies does not need to be uniform, and the mesh portion 6 may include narrow linear bodies 9a with a width of 100 μm or less, and wide linear bodies 9b with a width that is twice or more of the width of the narrow linear bodies 9a.
[0056] The island-shaped portion 5 has a shape that is wider than the width (length in a direction perpendicular to the length direction) of the linear body and is extended in a planar shape. In addition, the width of the short side direction of the island-shaped portion 5 is, for example, more than three times the width of the wide linear body. In the adhesive layer 4, the island-shaped portions 5 are formed dispersedly, but the intervals between adjacent island-shaped portions 5 may not be fixed, and there may be island-shaped portions 5 close to each other and island-shaped portions 5 far away from each other.
[0057] As described above, a plurality of linear bodies extend in various directions, and thus, voids 7 of various sizes are formed in the region around the island 5 where no linear bodies exist. The shape of the void 7 when viewed in the stacking direction has a flat circle or a polygon. A plurality of small-area voids 7 are formed in the region between the islands 5 that are close to each other, and a large-area void 7 is formed in the region between the islands 5 that are far away. In addition, in the present embodiment, the inorganic fiber sheet 3 is formed by alternately weaving horizontal threads and vertical threads composed of inorganic fibers.
[0058] Also like Figure 3 As shown in the figure, the adhesive layer 4 has a mesh portion 6, so a void portion 7 is formed between the thermal insulation material 2 and the inorganic fiber sheet 3 in a region where the island portion 5 and the mesh portion 6 do not exist. In addition, the inorganic particles 8 contained in the thermal insulation material 2 are indicated by dots in the figure, but the adhesive layer 4 includes a part of the inorganic particles 8. In addition, the organic material contained in the adhesive layer 4 intrudes into the region from the surface in contact with the adhesive layer 4 to the inside of the inorganic fiber sheet 3.
[0059] In the protective cover 1 of the present embodiment configured as described above, since the thermal insulation material 2 having thermal insulation performance is provided, excellent thermal insulation effect and fire prevention effect can be obtained. In addition, since the inorganic fiber sheet 3 is provided and joined to the thermal insulation material 2, when an object is damaged around the protective cover 1 and splashes, the thermal insulation material 2 can be protected by the inorganic fiber sheet 3. Therefore, damage to the thermal insulation material 2 can be suppressed, and excellent thermal insulation effect and fire prevention effect can be maintained.
[0060] Furthermore, in the present embodiment, the adhesive layer 4 that joins the heat insulating material 2 and the inorganic fiber sheet 3 has an island portion 5 that has a planarly extended shape, so that the heat insulating material 2 and the inorganic fiber sheet 3 can be well joined. In addition, since a gap portion 7 is formed between the heat insulating material 2 and the inorganic fiber sheet 3, the heat insulating performance can be further improved compared to the case where the two are bonded by an adhesive applied in a planar shape to one surface of the heat insulating material 2 or the inorganic fiber sheet 3. In addition, the adhesive layer 4 has gap portions 7 of various sizes, so when the protective cover 1 is not squeezed in the thickness direction, the large-sized gap portions 7 contribute to the improvement of the heat insulating property. In addition, when the protective cover 1 is squeezed in the thickness direction, the small-sized gap portions 7 are supported by the surrounding linear bodies, and the reduction in volume is suppressed, so that the heat insulating performance can be maintained.
[0061] Furthermore, in the present embodiment, since the mesh portion 6 has the characteristic shape as described above, even when the protective cover 1 is pressed or bent, the mesh portion 6 flexibly bends, and the inorganic fiber sheet 3 can be prevented from being separated from the thermal insulation material 2. In addition, if the linear body has a large width at the base portion close to the island portion 5, when the protective cover 1 is pressed or bent, the linear body and the island portion 5 can be prevented from being disconnected. As a result, the adhesive layer 4 can follow the change in the shape of the protective cover 1, and the inorganic fiber sheet 3 can be further prevented from being separated from the thermal insulation material 2.
[0062] Furthermore, by including the inorganic particles 8 included in the heat insulating material 2 in the adhesive layer 4 or allowing the organic material included in the adhesive layer 4 to penetrate into the inorganic fiber sheet 3 , the bonding strength between the heat insulating material 2 and the inorganic fiber sheet 3 can be further improved.
[0063] Hereinafter, the materials constituting the heat insulating material 2 , the inorganic fiber sheet 3 , and the adhesive layer 4 of the protective cover 1 according to the present embodiment will be described in detail.
[0064] 〔Thermal insulation〕
[0065] The heat insulating material 2 used in the protective cover of the present embodiment is not particularly limited as long as it has a heat insulating effect. As an index indicating the heat insulating effect, thermal conductivity can be cited, but in the present embodiment, the thermal conductivity of the heat insulating material 2 is preferably less than 1 (W / m·K), more preferably less than 0.5 (W / m·K), and more preferably less than 0.2 (W / m·K). Furthermore, the thermal conductivity of the heat insulating material 2 is more preferably less than 0.1 (W / m·K), more preferably less than 0.05 (W / m·K), and particularly preferably less than 0.02 (W / m·K).
[0066] The thermal conductivity of the heat insulating material 2 can be measured in accordance with the “Testing method for thermal conductivity of refractory materials” described in Japanese Industrial Standards JIS R 2251.
[0067] The heat insulating material 2 contains inorganic particles, and as other components, for example, a component containing at least one selected from inorganic fibers, organic fibers, and organic particles can be used. Specific examples of each are shown below.
[0068] <Inorganic particles>
[0069] As inorganic particles, single inorganic particles can be used, and two or more inorganic particles can also be used in combination. As the kind of inorganic particles, from the viewpoint of heat insulation effect, preferably use the particles consisting of at least one inorganic material selected from oxide particles, carbide particles, nitride particles and inorganic hydrate particles, more preferably use oxide particles. In addition, shape is not particularly limited yet, preferably comprises at least one selected from nanoparticles, hollow particles and porous particles, specifically, inorganic hollow balls such as silicon dioxide nanoparticles, metal oxide particles, microporous particles, hollow silicon dioxide particles, particles consisting of heat-expandable inorganic materials, particles consisting of water-containing porous bodies, etc. can also be used.
[0070] When the average secondary particle size of the inorganic particles is 0.01 μm or more, it is easy to obtain and the increase in manufacturing costs can be suppressed. In addition, when the average secondary particle size of the inorganic particles is 200 μm or less, the desired heat insulation effect can be obtained. Therefore, the average secondary particle size of the inorganic particles is preferably 0.01 μm or more and 200 μm or less, and more preferably 0.05 μm or more and 100 μm or less.
[0071] In addition, when two or more inorganic particles with different heat insulation effects are used in combination, the heat generating body can be cooled in multiple stages, and heat absorption can be exhibited in a wider temperature range. Specifically, it is preferred to mix large-diameter particles and small-diameter particles. For example, when nanoparticles are used as a kind of inorganic particles, it is preferred to include inorganic particles consisting of metal oxides as another inorganic particle. Hereinafter, the inorganic particles with small diameter are used as the first inorganic particles, and the inorganic particles with large diameter are used as the second inorganic particles, and the inorganic particles are described in more detail.
[0072] <First Inorganic Particles>
[0073] (Oxide particles)
[0074] When oxide particles are used as the first inorganic particles, radiative heat transfer can be suppressed, especially in high temperature areas such as abnormal heating. As oxide particles, at least one particle selected from silica, titania, zirconium oxide, zircon, barium titanate, zinc oxide and aluminum oxide can be used. That is, among the above-mentioned oxide particles that can be used as inorganic particles, only one type can be used, or two or more oxide particles can be used. In particular, silica is a component with high heat insulation, and titania is a component with a high refractive index compared to other metal oxides. It has a high effect of diffusely reflecting light and shielding radiant heat in high temperature areas above 500°C, so it is most preferred to use silica and titania as oxide particles.
[0075] In addition, oxide particles have a high refractive index and a strong effect of diffusely reflecting light, so the particle size of oxide particles may affect the effect of reflecting radiant heat. Therefore, when the average primary particle size of oxide particles is limited to a predetermined range, higher heat insulation can be obtained.
[0076] (Average primary particle size of oxide particles: 0.001 μm or more and 50 μm or less)
[0077] When the average primary particle size of the oxide particles is 0.001 μm or more, the particles are sufficiently larger than the wavelength of light that contributes to heating, so that the light is efficiently diffusely reflected. Therefore, in the high temperature region of 500°C or more, the radiation heat transfer of heat in the protective cover is suppressed, and the heat insulation can be further improved. On the other hand, when the average primary particle size of the oxide particles is 50 μm or less, even if compressed, the number of contact points between particles does not increase, and it is difficult to form a path for conductive heat transfer. Therefore, the influence on the heat insulation in the normal temperature region where conductive heat transfer is dominant can be reduced.
[0078] In the present invention, the average primary particle size can be determined by observing the particles with a microscope, comparing with a standard scale, and taking the average value of any 10 particles.
[0079] (Nanoparticles)
[0080] In the present invention, nanoparticles refer to nano-scale particles with an average primary particle size of less than 1 μm in a spherical or nearly spherical shape. Nanoparticles have low density, so they inhibit conductive heat transfer. If nanoparticles are used as the first inorganic particles, finer voids are dispersed, so that excellent thermal insulation that inhibits convective heat transfer can be obtained. Therefore, when a battery is used in a normal temperature range, nanoparticles are preferably used from the perspective of being able to inhibit heat conduction between adjacent nanoparticles.
[0081] Furthermore, if nanoparticles with a small average primary particle size are used as oxide particles, even when the thermal insulator is compressed due to the expansion of the battery cell accompanying thermal runaway and the internal density increases, the increase in the conductive heat transfer of the thermal insulator can be suppressed. The reason for this is believed to be that nanoparticles are easily repelled by static electricity to form fine gaps between particles, and the volume density is low, so the particles are filled in a manner that has a cushioning effect.
[0082] In addition, when nanoparticles are used as the first inorganic particles, the material is not particularly limited as long as it meets the above definition of nanoparticles. For example, silicon dioxide nanoparticles are a material with high heat insulation properties, and the contact points between the particles are small, so the heat conducted by the silicon dioxide nanoparticles becomes smaller than when using silicon dioxide particles with large particle sizes. In addition, the volume density of silicon dioxide nanoparticles usually obtained is 0.1 (g / cm 3 ), so even if a large compressive stress is applied to the thermal insulation, the size (area) and number of the contact points between the silica nanoparticles will not increase significantly, and the thermal insulation can be maintained. Therefore, as nanoparticles, silica nanoparticles are preferably used. As silica nanoparticles, wet silica, dry silica, and aerogel can be cited, and the silica nanoparticles that are particularly preferred in this embodiment are described below.
[0083] (Average primary particle size of nanoparticles: 1 nm or more and 100 nm or less)
[0084] When the average primary particle size of the nanoparticles is limited to a predetermined range, higher heat insulation properties can be obtained.
[0085] That is, when the average primary particle size of the nanoparticles is set to be greater than 1 nm and less than 100 nm, especially in a temperature range below 500° C., it is possible to suppress the convection heat transfer and conduction heat transfer of heat in the thermal insulation material, and the thermal insulation performance can be further improved. In addition, even when compressive stress is applied, the gaps remaining between the nanoparticles and the contact points between a large number of particles can suppress the conduction heat transfer, and the thermal insulation performance of the thermal insulation material can be maintained.
[0086] In addition, the average primary particle size of the nanoparticles is more preferably 2 nm or more, and further preferably 3 nm or more. On the other hand, the average primary particle size of the nanoparticles is more preferably 50 nm or less, and further preferably 10 nm or less.
[0087] (Inorganic hydrate particles)
[0088] When the inorganic hydrate particles are exposed to heat from the heating element and reach a temperature above the thermal decomposition start temperature, they undergo thermal decomposition, releasing their own crystal water to lower the temperature of the heating element and its surroundings, demonstrating the so-called "endothermic effect." In addition, after releasing the crystal water, they become porous and exhibit a heat-insulating effect through countless air pores.
[0089] Specific examples of inorganic hydrates include aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2), calcium hydroxide (Ca(OH)2), zinc hydroxide (Zn(OH)2), iron hydroxide (Fe(OH)2), manganese hydroxide (Mn(OH)2), zirconium hydroxide (Zr(OH)2) and gallium hydroxide (Ga(OH)3), etc.
[0090] For example, aluminum hydroxide has about 35% of crystal water, and as shown in the following formula, it undergoes thermal decomposition to release crystal water, exhibiting an endothermic effect. Moreover, after releasing the crystal water, it becomes alumina (Al2O3) as a porous body, which functions as a heat insulator.
[0091] 2Al(OH)3→Al2O3+3H2O
[0092] In a battery cell that has thermal runaway, the temperature rises rapidly to over 200° C. and continues to rise to around 700° C. Therefore, the inorganic particles contained in the thermal insulator 2 are preferably composed of inorganic hydrates having a thermal decomposition starting temperature of 200° C. or higher.
[0093] Regarding the thermal decomposition starting temperatures of the inorganic hydrates listed above, aluminum hydroxide is about 200°C, magnesium hydroxide is about 330°C, calcium hydroxide is about 580°C, zinc hydroxide is about 200°C, iron hydroxide is about 350°C, manganese hydroxide is about 300°C, zirconium hydroxide is about 300°C, and gallium hydroxide is about 300°C. They all roughly overlap with the temperature range of the rapid temperature rise of the battery cell that has thermal runaway, and can effectively suppress the temperature rise. Therefore, they can be said to be preferred inorganic hydrates.
[0094] (Average secondary particle size of inorganic hydrate particles: 0.01 μm or more and 200 μm or less)
[0095] In addition, when inorganic hydrate particles are used as the first inorganic particles, if the average particle size is too large, it takes a certain amount of time for the first inorganic particles (inorganic hydrate) located near the center of the thermal insulation material 2 to reach their thermal decomposition temperature, so that the first inorganic particles near the center of the thermal insulation material 2 may not be completely thermally decomposed. Therefore, the average secondary particle size of the inorganic hydrate particles is preferably 0.01 μm or more and 200 μm or less, and more preferably 0.05 μm or more and 100 μm or less.
[0096] (Particles composed of heat-expandable inorganic material)
[0097] Examples of the thermally expandable inorganic material include vermiculite, bentonite, mica, and perlite.
[0098] (Particles composed of a porous body containing water)
[0099] Specific examples of the hydrous porous body include zeolite, kaolinite, montmorillonite, acid clay, diatomaceous earth, wet silica, dry silica, aerogel, mica, vermiculite and the like.
[0100] (Inorganic hollow sphere)
[0101] The heat insulating member 2 used in the present invention may contain inorganic hollow spheres as the first inorganic particles.
[0102] When the inorganic hollow spheres are included, convection heat transfer or conductive heat transfer of heat in the thermal insulation material 2 can be suppressed in a temperature range lower than 500° C., and the thermal insulation property of the thermal insulation material 2 can be further improved.
[0103] As the inorganic hollow balloon, at least one selected from the group consisting of white sand balloon, silica balloon, fly ash balloon, barite balloon, and glass balloon can be used.
[0104] (Content of inorganic hollow spheres: 60% by mass or less relative to the total mass of the thermal insulation material)
[0105] The content of the inorganic hollow spheres is preferably 60% by mass or less based on the total mass of the thermal insulation material.
[0106] (Average particle size of inorganic hollow spheres: 1 μm or more and 100 μm or less)
[0107] The average particle size of the inorganic hollow spheres is preferably 1 μm or more and 100 μm or less.
[0108] <Second Inorganic Particles>
[0109] <Second Inorganic Particles>
[0110] When two kinds of inorganic particles are contained in the thermal insulation member 2, the second inorganic particles are not particularly limited as long as they are different from the first inorganic particles in material, particle size, etc. As the second inorganic particles, oxide particles, carbide particles, nitride particles, inorganic hydrate particles, silica nanoparticles, metal oxide particles, inorganic hollow spheres such as microporous particles or hollow silica particles, particles composed of thermally expandable inorganic materials, particles composed of water-containing porous bodies, etc. can be used, and their details are as described above.
[0111] In addition, the conductive heat transfer of nanoparticles is extremely small, and even when compressive stress is applied to the thermal insulation, it is possible to maintain excellent thermal insulation. In addition, metal oxide particles such as titanium dioxide are highly effective in blocking radiant heat. Furthermore, if large-diameter inorganic particles and small-diameter inorganic particles are used, the small-diameter inorganic particles will enter the gaps between the large-diameter inorganic particles, thereby forming a denser structure, which can improve the thermal insulation effect. Therefore, when, for example, nanoparticles are used as the above-mentioned first inorganic particles, it is preferred that the thermal insulation further contain particles composed of metal oxides having a diameter greater than the first inorganic particles as second inorganic particles.
[0112] Examples of the metal oxide include silicon oxide, titanium oxide, aluminum oxide, barium titanate, zinc oxide, zircon, zirconium oxide, etc. In particular, titanium oxide (titanium dioxide) is a component having a higher refractive index than other metal oxides, and has a high effect of diffusely reflecting light and shielding radiant heat in a high temperature range of 500° C. or higher, so titanium dioxide is most preferably used.
[0113] When at least one particle selected from silica nanoparticles and silica aerogels is used as the first inorganic particle and at least one particle selected from titanium dioxide, zircon, zirconium oxide, silicon carbide, zinc oxide and aluminum oxide is used as the second inorganic particle, in order to obtain excellent thermal insulation performance within a temperature range of 90° C. or less, the first inorganic particle is preferably 50% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more relative to the total mass of the inorganic particles. In addition, the first inorganic particle is preferably 95% by mass or less, more preferably 90% by mass or less, and further preferably 80% by mass or less relative to the total mass of the inorganic particles.
[0114] On the other hand, in order to obtain excellent thermal insulation performance in a temperature range exceeding 90° C., the second inorganic particles are preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 20% by mass or more relative to the total mass of the inorganic particles. In addition, the second inorganic particles are preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less relative to the total mass of the inorganic particles.
[0115] (Average primary particle size of the second inorganic particles)
[0116] When the thermal insulation material contains second inorganic particles composed of metal oxide, if the average primary particle size of the second inorganic particles is 1 μm or more and 50 μm or less, radiant heat transfer can be effectively suppressed in a high temperature region of 500° C. or more. The average primary particle size of the second inorganic particles is more preferably 5 μm or more and 30 μm or less, and most preferably 10 μm or less.
[0117] (Content of Inorganic Particles)
[0118] In the present embodiment, if the total content of the inorganic particles in the heat insulating material 2 is appropriately controlled, the heat insulating property of the heat insulating material 2 can be sufficiently ensured.
[0119] The total content of inorganic particles is preferably 60% by mass or more, and more preferably 70% by mass or more, relative to the total mass of the thermal insulation member. In addition, when the total content of inorganic particles is too much, the content of organic fibers will be relatively reduced. Therefore, in order to fully obtain the reinforcement effect of the skeleton and the retention effect of the inorganic particles, the total content of inorganic particles is preferably 95% by mass or less, and more preferably 90% by mass or less, relative to the total mass of the thermal insulation member.
[0120] The content of the inorganic particles in the thermal insulation material can be calculated, for example, by heating the thermal insulation material at 800° C. to decompose the organic components and then measuring the mass of the remaining components.
[0121] <Inorganic Fiber>
[0122] As the inorganic fiber, a single inorganic fiber may be used, or two or more inorganic fibers may be used in combination. Examples of the inorganic fiber include: As the inorganic fiber, examples include: silica fiber, alumina fiber, aluminum silicate fiber, zirconium oxide fiber, carbon fiber, soluble fiber, refractory ceramic fiber, aerogel composite material, magnesium silicate fiber, alkaline earth silicate fiber, potassium titanate fiber, silicon carbide fiber, potassium titanate whisker fiber and other ceramic fibers, glass fiber, glass wool, slag wool and other glass fibers, rock wool, basalt fiber, wollastonite, mullite fiber and other natural mineral fibers, etc.
[0123] These inorganic fibers are preferred in terms of heat resistance, strength, availability, etc. Among the inorganic fibers, from the viewpoint of handling, it is particularly preferred that the inorganic fibers be composed of at least one selected from silica fibers, alumina fibers, aluminum silicate fibers, zirconia fibers, glass fibers, and natural mineral fibers other than these fibers.
[0124] The cross-sectional shape of the inorganic fiber is not particularly limited, and examples thereof include circular cross-section, flat cross-section, hollow cross-section, polygonal cross-section, core cross-section, etc. Among them, fibers with a hollow cross-section, flat cross-section or polygonal cross-section are preferably used because they have slightly higher heat insulation properties.
[0125] (Average fiber length of inorganic fibers)
[0126] The preferred lower limit of the average fiber length of the inorganic fibers is 0.1 mm, and the more preferred lower limit is 0.5 mm. On the other hand, the preferred upper limit of the average fiber length of the inorganic fibers is 50 mm, and the more preferred upper limit is 10 mm. If the average fiber length of the inorganic fibers is less than 0.1 mm, it is difficult to produce entanglement between the inorganic fibers, and the mechanical strength of the thermal insulation may be reduced. On the other hand, if the average fiber length of the inorganic fibers exceeds 50 mm, although a reinforcement effect can be obtained, the inorganic fibers can be tightly entangled with each other, or curled only by a single inorganic fiber, which may lead to a reduction in thermal insulation.
[0127] The preferred lower limit of the average fiber diameter of the inorganic fibers is 1 μm, the more preferred lower limit is 2 μm, and the further preferred lower limit is 3 μm. On the other hand, the preferred upper limit of the average fiber diameter of the inorganic fibers is 15 μm, and the more preferred upper limit is 10 μm. When the average fiber diameter of the inorganic fibers is less than 1 μm, the mechanical strength of the inorganic fibers themselves may be reduced. In addition, from the viewpoint of the impact on human health, the average fiber diameter of the inorganic fibers is preferably greater than 3 μm. On the other hand, when the average fiber diameter of the inorganic fibers is greater than 15 μm, the solid heat transfer using the inorganic fibers as the medium will increase, which may lead to a decrease in thermal insulation. In addition, the formability and strength of the thermal insulation may deteriorate.
[0128] (Inorganic fiber content)
[0129] In the present embodiment, when the heat insulating material 2 contains inorganic fibers, the content of the inorganic fibers is preferably 3% by mass or more and 15% by mass or less relative to the total mass of the heat insulating material.
[0130] In addition, the content of inorganic fibers is more preferably 5% by mass or more and 10% by mass or less relative to the total mass of the thermal insulation member. By setting such a content, the shape retention, compression resistance, wind pressure resistance, and inorganic particle retention capacity of the inorganic fibers are balanced. In addition, by appropriately controlling the content of inorganic fibers, organic fibers and inorganic fibers are entangled with each other to form a three-dimensional network, thereby further improving the effect of retaining inorganic particles and other compounding materials described later.
[0131] <Organic Fiber>
[0132] Organic fibers have the effect of imparting flexibility to the thermal insulation material, and by forming a skeleton with organic fibers, the strength of the thermal insulation material is increased. In addition, when inorganic particles and other organic fibers are fused to the surface of the organic fibers, the effect of enhancing the strength of the thermal insulation material and the effect of maintaining the shape can be further improved. In addition, if the thermal insulation material contains organic fibers at an appropriate content, a plurality of voids are formed inside the thermal insulation material, and when the thermal insulation material is heated, air and moisture can be released to the outside through the voids.
[0133] As a material of the organic fiber in the heat insulating material 2, in addition to single-component organic fibers such as cellulose fibers, polyvinyl alcohol (PVA) fibers, polyethylene fibers, nylon fibers, polyurethane fibers, ethylene-vinyl alcohol copolymer fibers, and the like can be used.
[0134] When the thermal insulation material is produced by a papermaking method, it is difficult to increase the heating temperature to higher than 250° C., so the glass transition temperature of the organic fiber is preferably 250° C. or lower, more preferably 200° C. or lower.
[0135] The lower limit of the glass transition temperature of the organic fiber is not particularly limited, but when a resin binder is used, if the difference between the glass transition temperature of the resin binder and the glass transition temperature of the resin binder is 10°C or more, the resin binder will solidify after the semi-molten organic fiber is completely solidified during the cooling process during the manufacturing process, so the reinforcing effect of the resin binder on the skeleton can be fully obtained. Therefore, the difference between the glass transition temperature of the resin binder and the glass transition temperature of the organic fiber is preferably 10°C or more, and more preferably 30°C or more.
[0136] On the other hand, when the difference between the glass transition temperatures of the two is 130°C or less, the time from when the organic fiber is completely cured to when the resin binder starts to cure can be appropriately adjusted, and the resin binder is cured in a well-dispersed state, so that the reinforcement effect of the skeleton can be further obtained. Therefore, the difference between the glass transition temperature of the resin binder and the glass transition temperature of the organic fiber is preferably 130°C or less, more preferably 120°C or less, further preferably 100°C or less, further more preferably 80°C or less, and particularly preferably 70°C or less.
[0137] As the organic fiber, a core-sheath structured binder fiber may also be used. The core-sheath structured binder fiber has a core extending in the longitudinal direction of the fiber and a sheath formed in a manner covering the outer peripheral surface of the core. In this case, the core is made of a first organic material, the sheath is made of a second organic material, and the melting point of the first organic material is higher than the melting point of the second organic material.
[0138] (First organic material)
[0139] In this embodiment, when using a core-sheath structured binder fiber, the first organic material constituting the core is not particularly limited as long as it has a higher melting point than the sheath present on the outer peripheral surface of the core, i.e., the second organic material. The first organic material may be at least one selected from polyethylene terephthalate, polypropylene, and nylon.
[0140] (Second organic material)
[0141] The second organic material is not particularly limited as long as it has a lower melting point than the first organic material constituting the organic fiber. The second organic material may be at least one selected from polyethylene terephthalate, polyethylene, polypropylene, and nylon.
[0142] The melting point of the second organic material is preferably 90° C. or higher, and more preferably 100° C. or higher. The melting point of the second organic material is preferably 150° C. or lower, and more preferably 130° C. or lower.
[0143] (Organic fiber content)
[0144] If the content of the organic fibers in the heat insulating material 2 is appropriately controlled, a sufficient reinforcement effect of the skeleton can be obtained.
[0145] The content of organic fibers is preferably 5% by mass or more, and more preferably 10% by mass or more, relative to the total mass of the thermal insulation member. In addition, if the content of organic fibers is too high, the content of inorganic particles will be relatively reduced. Therefore, in order to obtain the desired thermal insulation performance, the content of organic fibers is preferably 25% by mass or less, and more preferably 20% by mass or less, relative to the total mass of the thermal insulation member.
[0146] (Fiber length of organic fibers)
[0147] The fiber length of the organic fibers is not particularly limited, but from the viewpoint of ensuring moldability and processability, the average fiber length of the organic fibers is preferably 10 mm or less.
[0148] On the other hand, from the viewpoint of allowing the organic fibers to function as a skeleton and ensuring the compressive strength of the thermal insulating material, the average fiber length of the organic fibers is preferably 0.5 mm or more.
[0149] (Non-melting fiber)
[0150] The heat insulating material 2 may also contain infusible fibers as fibers. Examples of infusible fibers include fibers obtained by infusible treatment of thermoplastic resins such as polyacrylonitrile, cellulose, and asphalt. Infusible fibers refer to fibers obtained by infusible treatment, for example. Infusible treatments include methods of crosslinking by irradiation with radiation, electron beams, etc., and methods of exposing to high temperatures in oxygen and water vapor and infusible by the action of oxygen.
[0151] (Carbon content)
[0152] The carbon content of the infusible fiber is preferably 55% to 95% by mass. If the carbon content is 55% by mass or more, the weight loss caused by thermal decomposition is already in progress, so the shrinkage caused by thermal decomposition is small, and in the case of thermal runaway, even if directly exposed to flames, it can maintain its original shape and maintain thermal insulation. If the carbon content is 95% by mass or less, the components other than carbon are separated and changed into a structure with only carbon, so an endothermic reaction occurs, so the time for heat to reach the back of the fireproof structure can be delayed.
[0153] The lower limit of the carbon content is preferably 60% by mass or more. The upper limit of the carbon content is preferably 90% by mass or less, and the upper limit of the carbon content is more preferably 85% by mass or less.
[0154] The carbon content can be adjusted by heat treatment. For example, heat treatment in the air or in oxygen at a temperature of 150 to 300°C can further promote infusibility and remove components other than carbon to increase the carbon content. For example, heat treatment at a temperature of 300 to 1000°C can promote the formation of condensed polycyclic aromatic structures and generate decomposition gases to increase the carbon content.
[0155] In addition, the infusible fibers are not limited to those obtained by infusible thermoplastic fibers, and may be inorganic fibers as long as the carbon content is within the above-mentioned range.
[0156] (Fiber shape)
[0157] The infusible fibers are preferably composed of short fibers. The so-called short fibers are not continuous fibers. In continuous fibers, the orientation direction of the fibers is consistent to form a fiber bundle, such as a fabric or a fiber winding. In contrast, by using short fibers, the fibers are oriented in random directions to form a collection (mat, felt, papermaking body). In addition, the conductive path of the thermal insulation using short fibers is short, so even if the fibers are carbonized or the carbonization is accompanied by thermal runaway, the conductivity can be reduced. In addition, the fibers are randomly oriented, and the fibers are easily in point contact with each other, which can reduce heat conduction.
[0158] When manufacturing a thermal insulation component containing infusible fibers, it is preferred to use ground fibers or chopped fibers (fiber length of about 0.01 mm to 10 mm) of the infusible fibers. In addition, the fiber diameter of the infusible fibers is preferably 1 μm to 30 μm. When the fiber diameter of the infusible fibers is 1 μm or more, even if exposed to high temperatures, the speed of air oxidation and sublimation can be suppressed, and the fireproof effect can be maintained for a long time. On the other hand, when the fiber diameter of the infusible fibers is 30 μm or less, even if exposed to high temperatures and carbonized, a certain degree of softness can be maintained, and even if deformation or impact occurs, it is not easy to be damaged.
[0159] <Organic particles>
[0160] As the organic particles, hollow polystyrene particles or the like can be used.
[0161] <Other matching materials>
[0162] (resin adhesive)
[0163] The material of the heat insulating member 2 in this embodiment may also be bonded by a resin adhesive. The resin adhesive is not particularly limited as long as it has a glass transition temperature lower than the glass transition temperature of the above-mentioned single-component organic fiber. For example, a resin adhesive containing at least one selected from styrene-butadiene resin, acrylic resin, silicone-acrylic resin and styrene resin can be used.
[0164] The glass transition temperature of the resin binder is not particularly specified, but is preferably -10°C or higher. In addition, when the glass transition temperature of the resin binder is room temperature or higher, when the heat insulating material having the resin binder is used at room temperature, the strength of the heat insulating material can be further improved. Therefore, the glass transition temperature of the resin binder is, for example, more preferably 20°C or higher, more preferably 30°C or higher, further preferably 50°C or higher, and particularly preferably 60°C or higher.
[0165] The content of the resin binder is preferably 0.5% by mass or more, more preferably 1% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less, based on the total mass of the thermal insulation material.
[0166] (Hot-melt powder)
[0167] In the mixture used to manufacture the thermal insulation member 2, in addition to the above-mentioned inorganic particles, inorganic fibers, organic fibers, and organic particles, hot-melt powder may also be contained. In the case of using the above-mentioned core-sheath structured binder fiber, the hot-melt powder, for example, contains a third organic material different from the above-mentioned first organic material and second organic material, and is a powder having the property of melting by heating. By including hot-melt powder in the material mixture of the thermal insulation member 2 and heating it, the hot-melt powder melts and then solidifies while containing the surrounding inorganic particles when cooled. Therefore, it is possible to further suppress the inorganic particles from falling off from the thermal insulation member.
[0168] As the hot-melt powder, there are hot-melt powders with various melting points. Considering the melting points of the core and sheath of the adhesive fiber to be used, a hot-melt powder with an appropriate melting point can be selected. In the case of using an adhesive fiber with a core-sheath structure as an organic fiber, if the third organic material as a component constituting the hot-melt powder has a lower melting point than the first organic material constituting the organic fiber, a heating temperature can be set to melt the sheath and the hot-melt powder while leaving the core. For example, if the melting point of the hot-melt powder is lower than the melting point of the sheath, the heating temperature during manufacturing can be set between the melting point of the core and the melting point of the sheath, so that the heating temperature can be set more easily.
[0169] On the other hand, the type of hot-melt powder used can also be selected in such a way that the melting point of the hot-melt powder is between the melting point of the core and the melting point of the sheath. If a hot-melt powder with such a melting point is used, when the sheath and the hot-melt powder are melted and then cooled and solidified, the hot-melt powder in the gap between the organic fiber (core) and the molten sheath and inorganic particles around it solidifies first. As a result, the position of the organic fiber can be fixed, and then the molten sheath is welded to the organic fiber, thereby easily forming a three-dimensional skeleton. Therefore, the overall strength of the thermal insulation can be further improved.
[0170] If the melting point of the third organic material constituting the hot-melt powder is sufficiently lower than the melting point of the first organic material constituting the core, the setting margin of the heating temperature in the heating process can be expanded, and the temperature setting for obtaining the desired structure can be performed more easily. For example, the melting point of the first organic material is preferably higher than the melting point of the third organic material by 60°C or more, more preferably higher by 70°C or more, and further preferably higher by 80°C or more.
[0171] The melting point of the hot-melt powder (third organic material) is preferably 80° C. or higher, more preferably 90° C. or higher. The melting point of the hot-melt powder (third organic material) is preferably 180° C. or lower, more preferably 150° C. or lower. Components constituting the hot-melt powder include polyethylene, polyester, polyamide, ethylene vinyl acetate, and the like.
[0172] (Content of hot melt powder)
[0173] When hot-melt powder is included in the material of the thermal insulation member in order to suppress the falling of inorganic particles, the effect of suppressing the falling of powder can be obtained even if the content is a trace amount. Therefore, the content of hot-melt powder is preferably 0.5% by mass or more, and more preferably 1% by mass or more relative to the total mass of the material constituting the thermal insulation member.
[0174] On the other hand, if the content of hot-melt powder is increased, the content of inorganic particles, etc. will be relatively reduced. Therefore, in order to obtain the desired thermal insulation performance, the content of hot-melt powder is preferably less than 5 mass%, and more preferably less than 4 mass% relative to the total mass of materials constituting the thermal insulation member.
[0175] In the case of a material containing hot-melt powder as the heat insulating member, the heating temperature in the heating process is preferably set to be 10°C or higher than the higher one of the melting point of the second organic material constituting the sheath and the melting point of the third organic material constituting the hot-melt powder, and more preferably set to be 20°C or higher. On the other hand, the heating temperature is preferably set to be 10°C or lower than the melting point of the first organic material constituting the core, and more preferably set to be 20°C or lower. By setting the heating temperature to such a temperature, a strong skeleton can be formed, the strength of the heat insulating member can be further improved, and the inorganic particles can be prevented from falling off.
[0176] Furthermore, the thermal insulation material may contain other binders, colorants, etc. as necessary. These are useful for reinforcing the thermal insulation material, improving the moldability, etc., and the total amount is preferably 10% by mass or less relative to the total mass of the thermal insulation material.
[0177] In the present invention, the manufacturing method of the heat insulating member 2 is not particularly limited, and the heat insulating member 2 can be manufactured by the commonly used wet method and dry method. As for the materials used in the manufacturing process, the materials suitable for the manufacturing method can be selected from the materials listed above according to the required properties.
[0178] 〔Inorganic fiber sheet〕
[0179] The inorganic fiber sheet 3 in this embodiment is obtained by processing inorganic fibers into a sheet shape, and the inorganic fibers used are not particularly limited. For example, the inorganic fibers described in the above-mentioned thermal insulation member 2 can also be used. Among them, silica fibers, alumina fibers, glass fibers, and metal fibers are preferably used in view of low price, excellent handling, and high heat resistance.
[0180] In addition, regarding the inorganic fibers, there are no restrictions on the shape such as fiber diameter, etc. However, in consideration of preventing collision of splashes during thermal runaway, it is preferred that the holes are small.
[0181] [Adhesive layer]
[0182] The adhesive layer 4 in this embodiment contains an organic material. The adhesive layer 4 in this embodiment is formed by, for example, placing an adhesive material composed of an organic material between the thermal insulation member 2 and the inorganic fiber sheet 3, and heating and pressurizing the adhesive material. At this time, since the inorganic particles 8 in the thermal insulation member 2 are impregnated into the adhesive layer 4, the adhesive layer 4 also contains the inorganic particles 8. The content of the organic material is preferably 80% by mass or more relative to the total mass of the adhesive layer.
[0183] The organic material is not particularly limited, and synthetic rubber, polyolefin organic material, polyamide organic material, polyurethane organic material, etc. can be cited, wherein at least one of polyolefin organic material and polyamide organic material is preferably included. In particular, when polyolefin organic material is used, an adhesive layer can be provided at a low cost, and when polyamide organic material is used, the bonding strength can be improved. Therefore, the material of the adhesive layer can be selected according to the required characteristics.
[0184] In addition, as polyolefin organic materials, specifically, polyethylene and polypropylene can be cited. These materials have properties such as flexibility, shock absorption, softness, low rigidity, easy deformation, and ability to be stretched into a film. Therefore, polyethylene and polypropylene can be suitable as the material of the adhesive layer in this embodiment.
[0185] [Manufacturing method of protective cover]
[0186] Figure 4 Schematic diagram showing an example of a method for manufacturing a protective cover according to an embodiment of the present invention. Figure 4 , the manufacturing method of the protective cover is described in order of processes.
[0187] <Configuration process>
[0188] The placement step is a step of placing an adhesive material constituting an adhesive layer between the heat insulating material and the inorganic fiber sheet. Specifically, an inorganic fiber sheet 12 is pulled out from a wound sheet roll 11, and while being moved in a horizontal direction, a fibrous adhesive material 14 is ejected from a plurality of nozzles 13 disposed above the inorganic fiber sheet 12. Thereafter, a heat insulating sheet 15 is placed on the inorganic fiber sheet 12 on which the adhesive material 14 is placed.
[0189] In the step of arranging the adhesive material 14 on the upper surface of the inorganic fiber sheet 12 , a plurality of fibrous adhesive materials 14 extending in a plurality of directions are arranged on the inorganic fiber sheet 12 in a state where at least a portion of them overlap each other.
[0190] <Joining process>
[0191] The joining process is a process of heating and pressurizing the area where the heat insulating material, adhesive material, and inorganic fiber sheet are stacked. Specifically, the inorganic fiber sheet 12, adhesive material 14, and heat insulating sheet 15 are further moved and passed between a set of hot rollers 16 arranged above and below them, thereby heating and pressurizing the area where they are stacked. Thereafter, the inorganic fiber sheet 12 and the heat insulating sheet 15 are joined by cooling.
[0192] In the above-mentioned joining process, the adhesive material 14 is expanded and fused in the overlapping areas to form Figure 2 The island-like portion 5 is shown. In the region where the island-like portion 5 is not formed, the adhesive material 14 is slightly expanded by pressure, but the fiber shape remains as it is, and the mesh-like portion 6 is formed.
[0193] <Forming process>
[0194] Then, the region where the inorganic fiber sheet 12 and the heat insulating sheet 15 are joined is cut by a cutting machine 17 or the like, thereby forming the inorganic fiber sheet 12 into a desired shape and size. Thus, the protective cover 1 in which the heat insulating material 2 and the inorganic fiber sheet 3 are joined via the adhesive layer 4 can be manufactured. The unnecessary portion after the cutting is wound up by the winding roll 18.
[0195] According to the above manufacturing method, the adhesive layer 4 having the island portion 5 and the mesh portion 6 can be easily formed, and the heat insulating material 2 and the inorganic fiber sheet 3 can be firmly bonded by the island portion 5. Figure 3 The gap 7 shown can further improve the heat insulation performance compared to the case where the heat insulating material 2 and the inorganic fiber sheet 3 are joined by a normal joining material.
[0196] In addition, the shape of the fibrous adhesive material 14 is not particularly limited. For example, the fibrous adhesive material 14 may be arranged irregularly like a nonwoven fabric. In addition, a plurality of fibrous adhesive materials 14 extending in a first direction, a second direction different from the first direction, and a third direction different from the first direction and the second direction may be arranged to overlap. In addition, a plurality of fibrous adhesive materials 14 may be arranged in a spiral or wavy shape.
[0197] In addition, in order to form the island-shaped portion 5, it is preferred to arrange the adhesive material 14 in such a manner that the arrangement amount of the fibrous adhesive material in the plurality of first regions is greater than the arrangement amount of the adhesive material in the other second regions. For example, the first region may be a region where a plurality of fibrous adhesive materials 14 overlap each other. In addition, in order to form the island-shaped portion 5, it is also possible to intentionally adjust the arrangement amount of the adhesive material 14 in the desired region (first region) to be greater.
[0198] The manufacturing method of the protective cover 1 is not limited to the above method. For example, a method may be adopted in which an adhesive sheet is prepared in advance as an adhesive material, and the adhesive sheet is arranged between the heat insulating member formed into a desired shape and the inorganic fiber sheet, and then heated and pressurized. The adhesive sheet is made of an organic material and can be made by processing a plurality of fibers extending in a plurality of directions into a sheet. In this case, the fibers made of the organic material can be arranged in such a way that the density of the fibers in the plurality of first regions is greater than the density of the fibers in the second region. For example, by forming a region where a plurality of fibers overlap each other, the region can be used as the first region.
[0199] [Battery module]
[0200] Figure 5 Schematic cross-sectional view of a battery module according to an embodiment of the present invention. Figure 5 As shown, the battery module 100 accommodates a plurality of storage batteries 110 in a battery case 120. In addition, the electrode terminals 111 of the storage batteries 110 are connected in series via a bus bar 130.
[0201] In addition, the battery case 120 has a top surface 120a, a side wall surface 120b, and a bottom wall surface 120c inside. The protective cover 1 of the present embodiment described above is attached to the entire surface of the top surface 120a of the battery case 120 by means of tape or the like. In addition, although not shown in the figure, the protective cover 1 is configured such that the inorganic fiber sheet in the protective cover 1 faces the electrode terminal 111, and the heat insulating member in the protective cover 1 faces the top surface side of the battery case 120.
[0202] In the battery module 100 thus configured, since the protective cover 1 has excellent heat insulation, even when the battery 110 thermally runs away and reaches a high temperature or catches fire, the heat transfer to the outside of the battery case 120 can be delayed. In addition, in the present embodiment, since the inorganic fiber sheet and the heat insulating material are joined with a high joining force, when the battery 110 ruptures due to thermal runaway, the inorganic fiber sheet does not fall off and protects the heat insulating material, and damage to the heat insulating material can be suppressed.
[0203] also, Figure 5 The battery module 100 shown has a protective cover 1 installed only on the top surface 120a of the battery housing 120, but the present invention is not limited to this structure. For example, by installing a protective cover 1 on at least one of the top surface 120a, the side wall surface 120b, and the bottom wall surface 120c of the battery housing 120, the transfer of heat to the outside of the battery housing 120 can be delayed. In addition, if the protective cover 1 is installed on all surfaces of the top surface 120a, the side wall surface 120b, and the bottom wall surface 120c of the battery housing 120, the heat insulation and fire resistance can be further improved. In addition, the protective cover 1 can also be installed between multiple batteries 110.
[0204] Above, various embodiments have been described, but the present invention is certainly not limited to such examples. It is clear to those skilled in the art that various variations or modifications can be thought of within the scope of the application documents, and it should be understood that they will naturally fall within the technical scope of the present invention. In addition, within the scope of not departing from the gist of the utility model, the various constituent elements in the above-mentioned embodiments may also be combined arbitrarily.
[0205] In addition, the present application is based on Japanese patent application (Japanese Patent Application No. 2023-053777) filed on March 29, 2023 and Japanese patent application (Japanese Patent Application No. 2024-018668) filed on February 9, 2024, the contents of which are incorporated herein by reference.
Claims
1. A protective cover, characterized in that: The protective cover has: Thermal insulation; Inorganic fiber sheets; as well as an adhesive layer that joins the thermal insulation member to the inorganic fiber sheet, When viewed in a lamination direction of the heat insulating material and the inorganic fiber sheet, the adhesive layer includes a plurality of island-shaped portions and a mesh-shaped portion connecting the plurality of island-shaped portions to each other.
2. The protective cover according to claim 1, characterized in that: A gap is provided between the inorganic fiber sheet and the thermal insulation material.
3. The protective cover according to claim 1, characterized in that: In the inorganic fiber sheet, the organic material constituting the adhesive layer intrudes into a region from a surface in contact with the adhesive layer to an inner region.
4. The protective cover according to claim 1, characterized in that: A part of the inorganic particles included in the thermal insulation material is impregnated into the adhesive layer.
5. A battery module, characterized in that: The battery module comprises: The protective cover according to any one of claims 1 to 4; Batteries; and A battery case houses the protective cover and the storage battery.
6. The battery module according to claim 5, characterized in that: The battery housing has a top surface, a side wall surface and a bottom wall surface inside. The protective cover is installed in the battery case and is arranged so that the heat insulating member faces at least one selected from the top surface, the side wall surface, and the bottom wall surface.
Citation Information
Patent Citations
Manufacturing method for manufacturing joined body
JP2023053777A
Game machine
JP2024018668A
Thermal barrier material for a rechargeable electrical energy storage system
WO2021022130A1